The ultra-thin AlN epitaxy on monolayer WS2 by helicon sputtering at 400 °C. (January 2023) - Huang, Yu-Che; Hsieh, Tung-Chen; Hong, Tz-Ju; Wu, Chia-Hsin; Ho, Yen-Teng; Tsai, Yi-Wei; Lin, Jhih-Min; Kao, Hui-Ling; Chang, Shu-Jui
Abstract: This work demonstrates the epitaxial growth of ultra-thin AlN films grown on monolayer WS2 /Sapphire by helicon sputtering. In our work, WS2 acts as a template to facilitate the initial two-dimensional (2D) AlN growth via van der Waals epitaxy (VDWE), and this growth method provides a promising semiconductor manufacturing process with low thermal budget (<450 °C) than the required for the backend-of-the-line (BEOL). The ultrathin AlN epitaxy on WS2 is characterized by synchrotron-based grazing-incidence wide-angle x-ray scattering (GIWAXS). There are two stages in AlN epitaxy on the WS2 ; the first is the layered AlN growth aligned with the underlying WS2 lattice. The subsequent development of AlN transforms into 3D growth, which is similar to Stranski–Krastanov (SK) mode. The ultrathin AlN films achieve atomic level smoothness and significant piezoelectric properties as indicated by the technique of atomic- and piezo force microscopy (AFM/PFM). This research broadens the application of 2D materials in assisting AlN epitaxy and has a potential avenue for hetero-epitaxial integration in developing future electronic devices. Highlights: Highly c-oriented AlN thin films grown on WS2 monolayer via van der Waals epitaxy at 400 °C low temperature is demonstrated. The growth mechanism of ultrathin AlN films on the WS2 is SK mode. The ultrathin AlN films achieve atomic level smoothness, uniformity, and significant piezoelectricity.